Adsorption Isotherms and Isosteric Heat of Adsorption of Metal Organic Frameworks as Gas Storage for Liquefied Petroleum Gas Vehicle in Iraq - Mohammed Sattar Jabbar,; Alrubaye, Rana Th. Abd (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
This research provides a novel technique for using metal organic frameworks (HKUST-1) as a gas storage system for liquefied petroleum gas (LPG) in Iraqi vehicles to avoid the drawbacks of the currently employed method of LPG gas storage. A low-cost adsorbent called HKUST-1 was prepared and characterized in this research to investigate its ability for propane storage at different temperatures (25, 30, 35, and 40 oC) and pressures of (1-7) bar. HKUST-1 was made using a hydrothermal method and characterized using powder X-ray diffraction, BET surface area, scanning electron microscopic (SEM), and Fourier Transforms infrared spectroscopy (FTIR). The HKUST-1 was produced using a hydrothermal technique and possesses a high crystallinity of up to 97%, surface area 3400 m2/g, and pore volume 0.7 cm3/g.  The prepared adsorbent (HKUST-1) tested using volumetric method, the maximum adsorption capacity of propane was (10.499 mmol/g) at a temperature of 298K and a pressure of 7 bar.  Furthermore, adsorption isotherm study was conducted to understand the system equilibrium (i.e., the fitting with one of the known models Langmuir, Freundlich, and Temkin isotherm models). It was observed that the Freundlich isotherm model fitted well the experimental data. The Clausius-Clapeyron equation was used to determine the heat of adsorption, and the results revealed that the heat of adsorption increased as the propane adsorption capacity increased. The prepared HKUST-1, which has a large surface area and a high adsorption capacity, can be used as a major solution for gas storage for liquefied petroleum gas (LPG) in Iraqi vehicles.